Effect of gender and gestational age on short term morbidities and mortality in extremely low birth neonates - Stuti Gagrani, Stuti Gagrani; Mehrotra, Gunjan; Mulye, Swati; Shrivastav, Aniket (International Journal of Contemporary Pediatrics, 2017)
Background: The Aim of this study was to see the effect of gender and gestational age on early morbidities and mortalities of extremely low birth weight neonates. Methods: It was cross section retrospective. This retrospective study over a period of 5 years from June 2009 to May 2014 in a tertiary level teaching hospital. All the ELBW neonates admitted during the study period were recruited. Moving in a retrospective manner we collected previous case records relevant to our study from the institute and then categorized our data on the basis of gestational age and gender, then we compared and analysed our data on the basis of incidence of mortalities and morbidities and the effect of gender and gestational age on it. Results: Out of 115 ELBW neonates 61(53%) were born at ≤ 28 weeks, 26 (22%) were born between 29 to 31 weeks and 28(24%) babies were born at 32 to 37 weeks. The most common maternal risk factors responsible for ELBW deliveries were Pregnancy induced hypertension 27 (23%) followed by premature rupture of membranes 20 (17%). Out of short term outcomes HMD (66%), Apnea (71%), hyperbilirubinemia (53%) and sepsis (54.7%) were most common comorbidities. There was no effect of gender on any short-term morbidity and mortality of ELBW newborns. There was a significant higher incidence of hyaline membrane disease, hypoglycemia and neonatal sepsis in ELBW neonates born before 28 weeks of gestational age as compared to born after 28 weeks. 50% of the neonates survived below 28 weeks of gestation. Conclusions: Our study shows the high incidence of short-term neonatal morbidities. ELBW neonates born before 28 weeks of gestation had higher morbidity.